Microscopic and Molecular Diagnosis of Mycobacterium Tuberculosis in Erbil city-Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study was carried out in consultation clinic of the Chest and Respiratory Diseases Center Erbil city-Iraq from  1st January to 31 December 2018.The results explained that from total of 1986 consecutive suspects with TB disease in Erbil city 103(%5.2) were pulmonary tuberculosis (PTB) infection depended on microscopic examination of sputum specimens with AFB stain and sputum culture on Lowenstein Jensen Media While   histopathology screening  (Biopsy- In cooperation with  histopathology's physician ) indicate that from 1883 (%94.8)  negative cases   8(%0.4) was  extrapulmonary tuberculosis (EPTB) infection. According to nationality, most cases were Iraqi from Erbil city52 (%50.5) while the number of non-national patients Syrian was 13(%68.4)and others were from different nationalities 6(%31.6), while Iraqi emigrant patients were 32(%31.1). According to age group, most cases were at age  group25-34 and 15-24years  were 27(%26.2) and 22(%21.3) respectively and only 2(% 1.9) patients were more than 65 years old. Most of the patients were male 55(%53.4) and 48 (%46.6) were females.Detection of  (TB) by GeneXpertMTB/RIF assay for contributing to the rapid diagnosis of the  disease and their resistance to drug rifampin (RIF) indicated that  all 103(%100) samples were positive to GeneXpertMTB the target DNA detected by real-time PCR which is needed to start treatment quickly,  while in 11(%10.6)   samples the Rifampicin  resistance DNA was detected which needs treatment with second-line agents. Conclusion: The results of the current study indicate that diagnosis and detection of TB  infection by microscopy, culture and rapid diagnosis by  PCR have the same accuracy.